Reconstructing Inclusive Political Communication Styles: The Function of Personal Figurations of Female Figures in Regional Leadership Through Systematic Literature Review - Anida Kusuma Ning Ariati; Anang Sujoko; Wawan Sobari (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study aimed to examine the political communication styles of female leaders in local governance by applying the concepts of personal figuration and inclusive communication based on mutual relations. Using a systematic literature review (SLR), the research analyzed 15 Scopus-indexed articles published between 2015 and 2025 that addressed themes of female leadership, political communication, and digital representation. The thematic analysis focused on three core issues: how leaders' lived experiences shaped their communication styles; which elements of inclusive, mutual communication were employed to build socio-political relations; and how digital strategies contributed to political legitimacy. The findings revealed that narratives of personal experience and community values strongly influenced the communication styles of local female leaders. They adopted empathetic and dialogical approaches to strengthen relationships with constituents and strategically used digital media as a space for affective, personalized political representation. The study concluded that women's political communication styles represented symbolic constructions rooted in social, gendered, and cultural contexts. These insights contributed to the development of gender-sensitive political communication theory and highlighted practical implications for female leadership strategies in the digital era.